2022
DOI: 10.3390/universe8020102
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on Barrow Entropy from M87* and S2 Star Observations

Abstract: We use data from M87* central black hole shadow, as well as from the S2 star observations, in order to extract constraints on Barrow entropy. The latter is a modified entropy arising from quantum-gravitational effects on the black hole horizon, quantified by the new parameter Δ. Such a change in entropy leads to a change in temperature, as well as to the properties of the black hole and its shadow. We investigate the photon sphere and the shadow of a black hole with Barrow entropy, and assuming a simple model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 110 publications
(68 reference statements)
1
24
0
Order By: Relevance
“…As we can observe, if we desire the baryon asymmetry to originate from the effects of the Barrow entropy in the Friedmann equations, we must require 0.005 ∆ 0.008. This interval is tighter than the one arising from cosmological datasets from Supernovae (SNIa) Pantheon sample and cosmic chronometers, namely ∆ = 0.0094 +0.094 −0.101 [40,41], as well as from the one obtained from M87* and S2 star observations, namely ∆ = 0.0036 +0.0792 −0.0145 [43], and it is slightly wider than the one from Big Bang Nucleosynthesis (BBN), i.e. ∆ 10 −4 [42].…”
Section: Baryon Asymmetry From Barrow Entropymentioning
confidence: 69%
See 2 more Smart Citations
“…As we can observe, if we desire the baryon asymmetry to originate from the effects of the Barrow entropy in the Friedmann equations, we must require 0.005 ∆ 0.008. This interval is tighter than the one arising from cosmological datasets from Supernovae (SNIa) Pantheon sample and cosmic chronometers, namely ∆ = 0.0094 +0.094 −0.101 [40,41], as well as from the one obtained from M87* and S2 star observations, namely ∆ = 0.0036 +0.0792 −0.0145 [43], and it is slightly wider than the one from Big Bang Nucleosynthesis (BBN), i.e. ∆ 10 −4 [42].…”
Section: Baryon Asymmetry From Barrow Entropymentioning
confidence: 69%
“…Additionally, one can apply Barrow entropy to the holographic principle, obtaining Barrow holographic dark energy [35][36][37][38][39]. Hence, one can confront the above constructions with observational data end amongst others extract constraints on the Barrow exponent ∆ [40][41][42][43]. As expected, in all these studies deviations from the BH entropy are found to be relatively small.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, in [14] the authors used observational data from Supernovae (SNIa) Pantheon sample, as well as from direct measurements of the Hubble parameter from the cosmic chronometers (CC) sample, in order to extract constraints on the scenario of Barrow holographic dark energy. It is important to notice that the BHDE has been widely studied in the literature, e.g., [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The first is to apply different horizons for the Universe, such as the event horizon, the apparent horizon, the age of the universe, the conformal time, the inverse square root of the Ricci curvature and the Gauss Bonnet term, etc [34][35][36][37][38][39][40][41][42][43][44][45]. On the other hand, the second possibility of modification is the consideration of a modified entropy expression for the Universe horizon instead of the standard Bekenstein-Hawking one, such as Tsallis entropy, Barrow entropy, Kaniadakis entropy, logarithmic corrected entropy etc [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%